Effect of calcium chloride and 4-aminopyridine therapy on desipramine toxicity in rats - Winai Wananukul (2018)
Background: Hypotension is a major contributor to mortality in tricyclic antidepressant overdose. Recent data suggest that tricyclic antidepressants inhibit calcium influx in some tissues. This study addressed the potential role of calcium channel blockade in tricyclic antidepressant-induced hypotension. Methods: Two interventions were studied that have been shown previously to improve blood pressure with calcium channel blocker overdose. CaCl2and 4-aminopyridine. Anesthetized rats received the tricyclic antidepressant desipramine IP to produce hypotension, QRS prolongation, and bradycardia. Fifteen min later, animals received CaCl2, NaHCO3, or saline. In a second experiment, rats received tricyclic antidepressant desipramine IP followed in 15 min by 4-aminopyridine or saline. Results: NaHCO3briefly (5 min) reversed hypotension and QRS prolongation. CaCl2and 4-aminopyridine failed to improve blood pressure. The incidence of ventricular arrhythmias (p = 0.004) and seizures (p = 0.03) in the CaCl2group was higher than the other groups. Conclusion: The administration of CaCl2or 4-aminopyridine did not reverse tricyclic antidepressant-induced hypotension in rats. CaCl2therapy may possibly worsen both cardiovascular and central nervous system toxicity. These findings do not support a role for calcium channel inhibition in the pathogenesis of tricyclic antidepressant-induced hypotension.